The use of MitraClip to prevent posttranscatheter aortic valve replacement left ventricular "suicide". Issue 2 (26th June 2020) - Bode, Michael F.; Ahmed, Andaleeb A.; Baron, Suzanne J.; Labib, Sherif B.; Gadey, Gautam
Abstract: Patients with concomitant severe aortic stenosis (AS) and left ventricular outflow tract (LVOT) obstruction undergoing transcatheter aortic valve replacement (TAVR) are at risk for hemodynamic collapse due to a sudden decrease in afterload causing worsening LVOT obstruction. We present a case of an 88‐year‐old female with symptomatic, severe AS, and LVOT obstruction with systolic anterior motion (SAM) of the mitral leaflet in whom alcohol septal ablation was contraindicated secondary to a chronic total occlusion of the right coronary artery that filled retrograde via septal collaterals. MitraClip at the time of TAVR was successfully performed to treat SAM with subsequent stabilization of LVOT gradients despite treatment of the patient's AS. This novel approach may represent a feasible option to prevent hemodynamic complications after TAVR in patients with significant LVOT obstruction secondary to SAM and AS.